A Novel Delay Spread Distribution Model for VHF and UHF Mobile-to-Mobile Channels - Fischer, Jörg Dieter; Heuberger, Albert; et al. (European Conference on Antennas and Propagation (EuCAP), 2013)
In this paper, the delay spread distribution of the mobile-to-mobile channel for various environments is analyzed based on new measurements in the frequency band from 30 MHz to 400 MHz. The results of the distribution are compared to the literature. In order to make the measurement results accessible for a simulation-based system design process, a new delay spread distribution model is proposed. This new model allows realistic estimates for the design and evaluation of mobile-to-mobile communication systems. © 2013 EurAA
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.anovel